Neonatal seizures and brain imaging - Bonifacio, Sonia L.; Miller, Steven P. (Journal of Pediatric Neurology, 2009)
Neonatal seizures are a symptom of brain dysfunction and frequently signal the clinician to look further for evidence of a pathologic intracranial or systemic process. Imaging the newborn brain is a critically important part of the evaluation of the newborn with seizures. Determining the underlying diagnosis is critical for appropriate treatment and accurately counseling the caregivers of affected newborns. Brain imaging provides the best aid in identification of causative brain abnormalities, including injury, and ultimately provides important insight into the prognosis of the newborn with seizures. Recent advances in specialized magnetic resonance techniques provide the opportunity to further study the effects of neonatal seizures in vivo, by measuring regional brain metabolism. As these advanced magnetic resonance imaging modalities can identify newborns at high risk of seizures, as well as those newborns at highest risk of adverse neurodevelopmental outcomes, they will further enable the study of emerging anti-seizure therapies on the newborn brain.
Keywords: Seizures; term newborn; asphyxia; hypoxic-ischemic encephalopathy; neonatal encephalopathy; stroke; MRI; MRS